A case report of a chronic migraine patient treated with three different anti-CGRP monoclonal antibodies: which parameters better represent the efficacy? - Uzun, Sena; Frejvall, Ulf; Özkaya-Sahin, Gülsen; Sahin, Gürdal (Frontiers in Neurology, 2023)
Objective To report the efficacy of different anti-calcitonin gene-related peptide (CGRP) monoclonal antibodies (mAbs) on headache frequency, intensity, and duration. Background Blockade of CGRP receptors or neuropeptide with anti-CGRP mAbs have been successfully used for several years for the prevention of chronic and episodic migraine. The response is usually assessed by improvement seen in the number of days with headache per month. However, clinical praxis indicates that sole reliance on the frequency of headaches might be insufficient to interpret the efficacy of these treatments. Methods Retrospective review of a case with a meticulous headache diary who has tried three different anti-CGRP mAbs for chronic migraine prevention. Results The patient has been diagnosed with chronic migraine and was first treated with erenumab, followed by fremanezumab and thereafter galcanezumab due to several reasons. In addition to significant improvement in all three parameters analyzed with anti-CGRP mAb treatment, the most important and valuable effect on the patient's quality of life was decreased duration and frequency of headaches. At present, the patient is receiving fremanezumab treatment with an excellent tolerability. Conclusion There is a clear need for careful follow-up and detailed daily records of headaches showing the frequency, duration, and severity for the evaluation of anti-CGRP mAbs treatment. This study shows the importance of this information in order for medical professionals to make an informed decision regarding the best course of anti-CGRP mAbs treatment in cases of side effects or lack of efficacy.